2021
DOI: 10.1259/bjrcr.20200133
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings in cervical spondylotic myelopathy with gadolinium enhancement: Review of seven cases

Abstract: Cervical spondylotic myelopathy (CSM) is a clinical syndrome secondary to a spinal cord compression due to cervical spondylosis. In some cases, conventional MRI typically shows an intramedullary hyperintense signal on T2W imaging and contrast enhancement on post-gadolinium T1W imaging. We report a series of seven patients with CSM who had typical clinical presentation and imaging findings on T2W and contrast-enhanced T1W sequences. The imaging findings included degenerative changes of the cervical spine, intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Other causes of myelopathy were also investigated and ruled out. 4 Regarding imaging findings, pancake enhancement of the cervical spine was first reported in 2014 by Flanagan et al 1 , who reported a similar case of upper extremity weakness and paresthesias. Since then, it has been acknowledged as an important, albeit rare, finding of compressive spondylotic myelopathy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other causes of myelopathy were also investigated and ruled out. 4 Regarding imaging findings, pancake enhancement of the cervical spine was first reported in 2014 by Flanagan et al 1 , who reported a similar case of upper extremity weakness and paresthesias. Since then, it has been acknowledged as an important, albeit rare, finding of compressive spondylotic myelopathy.…”
Section: Discussionmentioning
confidence: 93%
“…Dynamic imaging studies might be one of the keys to showing the cause. Other causes of myelopathy were also investigated and ruled out 4 …”
Section: Discussionmentioning
confidence: 99%
“…All 3 patients had T2WI changes whereas only 2 had T1WI changes on initial evaluation and were followed up at different time intervals. Two exhibited slow progression of their clinical symptoms, but the other exhibited partial recovery of symptoms 29. Despite the study’s obvious limitations, it hints that the clinical course from conservative management of DCM may not be readily predicted from MRI changes.…”
Section: Prognostic Factorsmentioning
confidence: 87%
“…Two exhibited slow progression of their clinical symptoms, but the other exhibited partial recovery of symptoms. 29 Despite the study's obvious limitations, it hints that the clinical course from conservative management of DCM may not be readily predicted from MRI changes. An example of patient deterioration during the course of nonoperative follow-up is seen in Figure 1.…”
Section: Spinal Cord Changes On Mrimentioning
confidence: 95%
“…Extradural mass (tumours), post-traumatic deformities, infections (tuberculosis), posttraumatic kyphosis, vascular disorders (vascular malformations, spinal cord infarct and epidural hematoma), nutritional disorders etc. could be some possible causes [14].…”
Section: Introduction Backgroundmentioning
confidence: 99%